2010
DOI: 10.1038/ejhg.2010.201
|View full text |Cite
|
Sign up to set email alerts
|

Relation of a common variant of the adiponectin gene to serum adiponectin concentration and metabolic traits in an aged Japanese population

Abstract: Adiponectin is an adipocyte-derived protein that is down-regulated in obesity-linked disorders. Variants of the adiponectin gene (ADIPOQ) have been shown to affect adiponectin level. We have now examined the relation of polymorphisms of ADIPOQ to adiponectin concentration and to metabolic disorders in the Kita-Nagoya Genomic Epidemiology study, a population-based study of elderly Japanese. The genomic region including ADIPOQ was genotyped for 30 single nucleotide polymorphisms in 500 subjects of a screening po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Nelson et al, manuscript in preparation). A different ADIPOQ missense variant (I164T) with low frequency in Japanese (MAF ¼ 0.009) has been shown to be associated with lower adiponectin levels (12), consistent with biochemical evidence that the I164T-containing adiponectin does not form trimers or high-molecular-weight multimers and impairs secretion from the adipocyte (17). However, we did not observe I164T or any other of seven known missense variants among the CLHNS samples.…”
Section: Discussionsupporting
confidence: 88%
“…Nelson et al, manuscript in preparation). A different ADIPOQ missense variant (I164T) with low frequency in Japanese (MAF ¼ 0.009) has been shown to be associated with lower adiponectin levels (12), consistent with biochemical evidence that the I164T-containing adiponectin does not form trimers or high-molecular-weight multimers and impairs secretion from the adipocyte (17). However, we did not observe I164T or any other of seven known missense variants among the CLHNS samples.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding links between rs266729 and MetS, early studies reported varying results. 27,28 The rs182052 was associated with an increased risk of the prevalence of obesity in adult Korean women, but there were no significant interactions observed between the genotype of ADIPOQ rs182052 and dietary intake on BMI and body fat mass. These findings suggest that the obesity-related variables may be more dominantly affected by the genotype of ADIPOQ rs182052 than dietary intake in middle-aged Korean women.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, our study observed relationship between psychological traits and EB that failed to reach statistical significance in the adjusted model. Though adiponectin gene is a known predictor of adiponectin concentrations in several populations (Hivert et al 2008;Cohen et al 2011;Tanimura et al 2011; de Luis et al 2016), we have no serum adiponectin levels available in the present study to confirm this in the young Nigerian population. Further studies are thus warranted to shed more light on the complexity of our results.…”
Section: Discussionmentioning
confidence: 45%